2014
DOI: 10.1016/j.alcr.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of intimate partnerships, sexual attitudes, desire and satisfaction

Abstract: This research addresses the interrelations existing between trajectories of intimate partnerships and attitudes toward sexuality, sexual desire, and sexual satisfaction. It is based on a dataset of 600 adults aged 25-46 living in Geneva (Switzerland) and uses innovative multivariate techniques for clustering life trajectories. The results emphasize the diversity of men's and women's trajectories of intimate partnerships. Trajectories with frequent and short-term partnerships are associated with recreational at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…On the one hand, having many partners may be a consequence of having a high sexual desire (Dawson & Chivers, 2014 ). On the other hand, a study led in Switzerland (Ammar et al, 2014 ) found that having had few or no intimate partners was correlated with a low sexual desire. An explanation may be that sexual desire drives sexual behavior and therefore, the higher the level of sexual desire, the higher the number of sexual partners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, having many partners may be a consequence of having a high sexual desire (Dawson & Chivers, 2014 ). On the other hand, a study led in Switzerland (Ammar et al, 2014 ) found that having had few or no intimate partners was correlated with a low sexual desire. An explanation may be that sexual desire drives sexual behavior and therefore, the higher the level of sexual desire, the higher the number of sexual partners.…”
Section: Discussionmentioning
confidence: 99%
“…The level of sexual desire may be related to a variety of factors such as socio-demographic ones (Ammar et al, 2014 ), health status (WHO, 2010 ), body image (Dosch et al, 2016a ), adolescence sexuality (Boislard et al, 2016 ), relationship status (Dawson & Chivers, 2014 ), level of sexual satisfaction (Dosch et al, 2016b ), sexual practices such as masturbation (Krejčová et al, 2017 ) and history of lifetime unwanted sexual experiences (Maseroli et al, 2018 ; Turchik & Hassija, 2014 ). Therefore, sexual desire is influenced by contextual, physiological and relationship factors which may affect females and males in different ways (Dawson & Chivers, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…There have been studies on non-probability samples to understand the trajectories and predictors of these trajectories. 21 , 22 …”
Section: Methodsmentioning
confidence: 99%
“…Bertogg and Szydlik 2016). A third approach lies in the life course perspective, in which family is studied in terms of family-related transitions and biographical phases (Ammar et al 2014;Elder 1977). However, there are no common overarching terminologies or heuristics available that are suitable for all research purposes trying to define or study 'family'.…”
Section: Introduction To the Topicmentioning
confidence: 99%